Mutagenesis of conserved tryptophan residues within the receptor-binding domain of intimin: influence on binding activity and virulence. - Reece, S; Simmons, C; Fitzhenry, R; Batchelor, M; Hale, C; Matthews, S; Phillips, A; Dougan, G; Frankel, G (2002)
Intimate bacterial adhesion to intestinal epithelium is a pathogenic mechanism shared by several human and animal enteric pathogens, including enteropathogenic and enterohaemorrhagic Escherichia coli and Citrobacter rodentium. The proteins directly involved in this process are the outer-membrane adhesion molecule intimin and the translocated intimin receptor, Tir. The receptor-binding activity of intimin resides within the carboxy terminus 280 aa (Int280) of the polypeptide. Four tryptophan residues, W117/776, W136/795, W222/881 and W240/899, are conserved within different Int280 molecules that otherwise show considerable sequence variation. In this study the influence of site-directed mutagenesis of each of the four tryptophan residues on intimin-Tir interactions and on intimin-mediated intimate attachment was determined. The mutant intimins were also studied using a variety of in vitro and in vivo infection models. The results show that all the substitutions modulated intimin activity, although some mutations had more profound effects than others.